PENGARUH KUALITAS PELAYANAN PERPAJAKAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Stefanus Irama Ndruru; Sovia Lolita Apriani Pardede; Mipo (Skena Bisnis, 2024)
ax is a mandatory levy which is one of the sources of state revenue that will be used to meet the interests of the general public. Obedience in paying taxes contributes to the achievement of targets set by the government, but not infrequently there are still many people's non-compliance in carrying out their obligations as taxpayers, especially for individual taxpayers. This study aims to determine the effect of service quality, modernization of the tax administration system and taxpayer awareness on individual taxpayer compliance at KPP Medan Barat.The population in this study were individual taxpayers registered at KPPMedan Barat, amounting to 218,474 people and from that number, 100 respondents were taken as samples. The variables in this study areservice quality (X1), modernization of the tax administration system (X2), taxpayer awareness (X3) and taxpayer compliance (Y). The data collection method is a questionnaire. The method of analysis is the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test. Multiple regression analysis, coefficient of determination test (R2) t test, F test.The results showed that respondents' responses to service quality, modernization of the tax administration system, awareness of taxpayers were very good and taxpayer compliance at KPP Pratama Medan Barat was also very high. The results of the t-test obtained p value <0.05 for the three independent variables with a positive correlation coefficient value of 0.000 each; 0.001; 0.000 for service quality variables, modernization of the tax administration system, taxpayer awareness. The explanatory power of these three variables on taxpayer compliance is 64.6%. The conclusion of this study is that service quality, modernization of the tax administration system and taxpayer awareness have a positive and significant impact on taxpayer compliance at KPP Medan Barat.